Comparing students’ self- assessment and teacher’s assessment on students ‘writings : - Nguyễn, Huỳnh Huế Thư (Trường đại học Cần Thơ, 2018)
This study aims to examine the results of student’s self- assessment in comparison to the results of teacher’s assessment on student’s writing. The goals of the present study were to explore whether there are differences between them in the assessment results.